Pricing of Medical Instrument Products for Domestic Production through Investment Feasibility Analysis - Hasbullah Hasbullah; Mohamad Nasir (ComTech: Computer, Mathematics and Engineering Applications, 2021)
Pricing products is an important factor to penetrate the Indonesian market successfully. Since Indonesia’s medical device products market has more than 90% import, local production companies must be competitive in price. The current pricing approach relies on the cost of sold goods, profit margin, and cost. Hence, a new pricing model is needed. The price from the new model must be better than the current price from the conventional pricing approach. The research aimed to formulate a pricing model for local medical device products that the market could accept and provide a framework model in local production pricing using investment feasibility analysis. The research used mathematical models, engineering economics, and pricing frameworks to optimize product prices from a local company (PT Enesser Mitra Berkah). The studied object was the domestic production of Anesthesia A8500. The research has several findings. First, the Break-Even Point (BEP) (X2) is an alternative standpoint to determine the price in a local production investment for medical device products. Second, the production company can consider the market price (X3). The research develops a simple mathematical model of X3 > Y2 = X2 + Ct > X1 (Y2 = new price, X1= cost of sold goods, Ct = profit and cost). The result provides the pricing framework model as a new approach for developing a medical device product price when the company initiates new local production.